Spotlight on ocular Kaposi's sarcoma: an update on the presentation, diagnosis, and management options. (2nd November 2021) - Venkateswaran, Nandini; Ramos, Juan C.; Cohen, Adam K.; Alvarez, Osmel P.; Cohen, Noah K.; Galor, Anat; Karp, Carol L.
ABSTRACT: Introduction: Kaposi's sarcoma (KS) is a multifocal low-grade vascular neoplasm that can affect the skin, mucus membranes, visceral organs, and lymph nodes. KS can also affect the ocular surface and adnexa and can masquerade as other entities, delaying prompt diagnosis. Areas covered: In this review, the manifestations of ocular KS are discussed along with theories for pathogenesis, common risk factors, and management options. Expert opinion: KS is caused by the oncogenic human herpesvirus 8 (HHV8). Immunosuppression in patients with HIV and AIDS contributes to the development of KS but conjunctival and ocular adnexal KS lesions are now uncommon in the era of anti-retroviral therapy. A high index of suspicion is required to diagnose ocular KS as these lesions can be mistaken for alternative entities. Prompt diagnosis can reduce significant morbidity and mortality by prompting a multidisciplinary systemic evaluation, particularly in immunosuppressed individuals. While surgical excision, cryotherapy, intralesional or systemic chemotherapy, and radiation are all viable treatment options, ongoing research to identify novel therapies and molecular treatment targets will help expand the armamentarium of therapeutics available for this disease.